Physical environment in school setting: conceptual reviews - Udin, Amirmudin; Rajuddin, Muhammad Rashid (2008)
Increasing numbers of educators have begun to believe that the physical environment might have an impact on students' outcomes. There are several research findings indicate that students academic outcomes are affected positively or adversely by the visual, acoustical, and thermal characteristics of the classroom environment (Bowers et al. 1987) such as student behavior (Cash, 1993); attitudes (Weinstein, 1979); and achievement (Cash, 1993; O’Sullivan, 2006); personality development (Roberts and Robins, 2004); student preferences and comfort (Corgnati et al., 2007). Concrete foundation is needed to discuss the circumstances of the physical environment in school setting. The valuable theorists mostly cited as a guidance is person-environment fit theory (Caplan and Van Harrison, 1993). The match between attributes of the person and attributes of the environment reflects the concept of person-environment (PE) fit (Roberts and Robins, 2004). This paper will reviews the related concept of physical environment from ergonomics perspectives which is mostly applied in workplaces setting in order to relate it with the condition or situation in classroom setting.